2012
DOI: 10.1021/cn300165x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Growth Defects in Mice with Constitutive Depletion of Central Serotonin

Abstract: Although the trophic actions of serotonin (5-HT) are well established, only few developmental defects have been reported in mouse strains with constitutive hyposerotonergia. We analyzed postnatal growth and cortical development in three different mutant mouse strains with constitutive reductions in central 5-HT levels. We compared two previously published mouse strains with severe (−95%) depletions of 5-HT, the tryptophan hydroxylase (Tph) 2 −/− mouse line and VMAT2 sert-cre mice, with a new strain, in which V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 58 publications
7
59
0
Order By: Relevance
“…Surprisingly, perinatal 5-HT deficiency only induces a reduction of barrel field organization without altering its general organization [177,207,208]. Nevertheless, further studies need to be carried since early reduction of 5-HT during embryonic development induces the emergence of altered behaviour [153].…”
Section: Serotonin and Axonal Development Within The Cerebral Cortexmentioning
confidence: 98%
See 1 more Smart Citation
“…Surprisingly, perinatal 5-HT deficiency only induces a reduction of barrel field organization without altering its general organization [177,207,208]. Nevertheless, further studies need to be carried since early reduction of 5-HT during embryonic development induces the emergence of altered behaviour [153].…”
Section: Serotonin and Axonal Development Within The Cerebral Cortexmentioning
confidence: 98%
“…For instance, mice deficient in Tph1 or Tph2 showed body weight reduction and delayed maturation of cortical layers [18,153,177]. Heterozygous embryos growing in null mutant Tph1 −/− mice showed an average of 30% reduction in proliferating cells (BrdU+) in the VZ after a 2 h pulse of BrdU administration, an analog of thymidine that is incorporated during the S phase of the cell cycle [18].…”
Section: Serotonin and Cell Proliferationmentioning
confidence: 99%
“…There are two isoforms of the enzyme; Tph1 which is predominantly expressed in the periphery, whereas Tph2 is predominantly expressed in the brain [38]. A Tph2 knockout in mice leads to retarded growth and lower body weight in early postnatal development [39,40]. An independent study found decreased food intake and bone mass in these mice [41] and the effects on body weight could possibly be gender dependent [42].…”
mentioning
confidence: 99%
“…11 Previous studies 11,13 examined Tph2 KO mice at 4 to 16 weeks of age, whereas Lexicon's mice were examined at 18 through 83 weeks of age. Tph2 KO mice have a transient growth retardation starting a few days after birth and lasting through 4 months of age 18,19 and limited data from Lexicon's KO mouse screening analyses 16 support this finding. Low trabecular bone Modest skeletal phenotypes in adult Tph2 KO mice R Brommage et al mass in studies examining growing mice is possibly related to their small size.…”
Section: Discussionmentioning
confidence: 99%